Flywheel energy storage - Er, Boon Yen (2010)
The project studies and demonstrates flywheel energy storage (FES) technologies system. The studies of flywheel energy storage technologies involve the past and the current FES technologies. The project mainly focuses on the principle and theory for flywheel energy storage.